A Critical Assessment on the Indonesian Free Visa Policy: a Neorealist Perspective - Indrady, Andry (UI Scholars Hub, 2020)
This paper discusses the implementation of free visa policy in Indonesia from a neorealist perspective. By utilizing the perspective of interdependence sovereignty and domestic sovereignty, this paper critically assesses the implementation of the free visa policy in Indonesia. From the interdependence sovereignty perspective, which elaborates the economic benefits, reciprocal and security approaches the paper finds that the free visa policy in Indonesia has yet to formulate a rational and objective policy that would lead to potential security – order threat. On the other hand, from the domestic sovereignty perspective the paper finds that although the state performs its immigration control capabilities effectively, however the said immigration control measures are implemented at a rather repressive level, instead of at the ideal prevention level. In the end, the paper suggests further research that fills the gap from findings on the specific methods to enhance the state’s capability in managing challenges posed by the free visa policy in more detail, as well as providing a method to measure public perception on the performance of immigration control.